2020
DOI: 10.1002/eji.201948336
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α and IL‐1β sensitize human MSC for IFN‐γ signaling and enhance neutrophil recruitment

Abstract: During inflammatory processes, tissue environmental cues are influencing the immunoregulatory properties of tissue‐resident mesenchymal stem/stromal cells (MSC). In this study, we elucidated one of the molecular and cellular responses of human MSC exposed to combinations of inflammatory cytokines. We showed that during multi‐cytokine priming by TNF‐α, IL‐1β, and IFN‐γ, IL‐1β further augmented the well‐established immunoregulatory activity induced by TNF‐α/IFN‐γ. On the molecular level, TNF‐α and IL‐1β enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…In a recent study, it was demonstrated that TNF-α/IFN-γ/IL-1β exposed MSCs had a stronger IL-8 secretion than MSCs exposed to TNF-α/IFN-γ only. Moreover, this increased expression of IL-8 enhanced neutrophil recruitment, a recruitment that was suggested to be mediated trough activation of STAT5 and p38-MAPK signaling (Hackel et al, 2020). This is but one example of potential means of pre-activating MSCs.…”
Section: Pre-activation Of Mesenchymal Stromal Cells Prior To Administrationmentioning
confidence: 89%
“…In a recent study, it was demonstrated that TNF-α/IFN-γ/IL-1β exposed MSCs had a stronger IL-8 secretion than MSCs exposed to TNF-α/IFN-γ only. Moreover, this increased expression of IL-8 enhanced neutrophil recruitment, a recruitment that was suggested to be mediated trough activation of STAT5 and p38-MAPK signaling (Hackel et al, 2020). This is but one example of potential means of pre-activating MSCs.…”
Section: Pre-activation Of Mesenchymal Stromal Cells Prior To Administrationmentioning
confidence: 89%
“…Furthermore, injection of IL-4 enhanced tumor clearance and correlated with increased infiltration of eosinophils, macrophages, neutrophils and in part lymphocytes. In addition, neutralizing IL-5 by monoclonal antibodies restored tumor growth (50,57,58,62,65). The latter studies demonstrated that Th2 cytokines are important in anti-tumor immunity, although they do not provide direct evidence for an involvement of Th2 cells.…”
Section: Th2 Cell-mediated Immunity To Tumorsmentioning
confidence: 96%
“…While, traditionally, type 2 immunity was implicated in an inhibition of anti-tumor responses, a number of studies provide convincing evidence demonstrating that Th2 cells indeed mediate anti-tumor immunity. Of note, these studies do not only provide correlative analyses, but apply adoptive Th2 cell transfer experiments (49,56,61) or perform pharmacological administration of Th2 cytokines to tumor bearing mice (50,57,58,62,66). Some of the anti-tumor effects of Th2 cells in addition were attributed to an indirect effect of Th2 cells and their cytokines on Th9 cells (98,99).…”
Section: Th2 Cell-mediated Immunity To Tumorsmentioning
confidence: 99%
“…Senescent MSCs were also unable to show protection in a murine model of LPS-induced lethal endotoxemia (155). In some reports, MSCs were indicated to enhance neutrophil recruitment and its bactericidal functions through TNF-a and IL-1b signaling (156,157). However, these findings highlight MSCs as a potential risk factor because aberrant neutrophil activation contributes to disease severity and local tissue damage in COVID-19 through the amplification of hypercytokinemia and the formation of neutrophil extracellular traps (NETs) (158).…”
Section: Adverse Effects Of Mscsmentioning
confidence: 99%